Analysis of Radioactive Isotope Concentrations at Various Locations after a Nuclear Disaster: Case Study of I-131, Cs-134, and Cs-137 in the Czech Republic - Rajagukguk, Michael Haratua; Siagian, Ruben Cornelius (Universitas Muhammadiyah Purwokerto, 2025)
Radioactive dispersal remains a major concern after a nuclear disaster. This study investigated the consistency of radioactive isotope concentrations (I-131, Cs-134, and Cs-137) in two cities in the Czech Republic - Prague and Usti - to determine whether sampling duration and isotope concentration variability affect contamination stability. The study used statistical analyses, including ANOVA, Kruskal-Wallis test, and Pearson and Spearman correlation tests, to examine isotope relationships and spatial variation. Data were collected over multiple time points to assess changes in contamination patterns. Findings showed that Prague exhibited higher concentrations of radioactive isotopes, but variations in sampling time did not affect contamination stability. No significant differences were observed between the two locations, and a strong correlation was found among I-131, Cs-134, and Cs-137, indicating that an increase in one isotope was consistently accompanied by an increase in the other. The sampling duration had no significant impact on the contamination levels. These results suggest that isotope contamination is stable across sites, regardless of sampling duration. A major research gap is the limited research on the relationship between consistency of isotope concentrations and sampling time across multiple sites. The study highlighted that radioactive isotope concentrations remained relatively consistent despite the large variability in measured values. Findings underscore the need for contamination management strategies that focus on globally significant sources rather than local variability. Strong correlations among isotopes offer potential predictive value for monitoring radioactive contamination in disaster situations.